2000
DOI: 10.1309/v8an-a2xp-7tdv-hr0t
|View full text |Cite
|
Sign up to set email alerts
|

Biclonal Chronic Lymphocytic Leukemia

Abstract: Chronic lymphocytic leukemia (CLL) is well characterized clinically and immunophenotypically. Demonstration of a monotypic CD19+, CD5+ B-cell population is central to the diagnosis. We report 2 cases of biclonal CLL. Two elderly men were encountered with an absolute lymphocytosis consisting of the typical CD5+, CD19+, CD23+ B-cell population seen in CLL; however, immunoglobulin light chain restriction by flow cytometry was not apparent as B cells expressed kappa or lambda light chains without a clear monotypic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 22 publications
1
20
0
1
Order By: Relevance
“…S5). Multiple separate clonal B-cell populations have been observed in previously published data in a subset of patients identified by different V and J chain usages (Hsi et al 2000;Boyd et al 2009), but the clinical significance of these findings are not known.…”
Section: Discussionmentioning
confidence: 98%
“…S5). Multiple separate clonal B-cell populations have been observed in previously published data in a subset of patients identified by different V and J chain usages (Hsi et al 2000;Boyd et al 2009), but the clinical significance of these findings are not known.…”
Section: Discussionmentioning
confidence: 98%
“…However, the development of new B-cell subclones resulting from the occurrence of additional genetic mutations in the neoplastic cells during the evolution of the disease has been described [35][36][37], with studies reporting CLL cases with two unrelated B-cell clones [9,[36][37][38][39]. In order to minimize the risk of including such cases in our series of patients with double productive IGHV rearrangements, we checked blood smear morphology and we run a four marker phenotypical panel as a requisite for inclusion in the study in all 60 patients.…”
Section: Discussionmentioning
confidence: 99%
“…1 In fact, in B-CLPD oligoclonality has been usually related to the development of new B-cell subclones resulting from the occurrence of additional genetic abnormalities on the neoplastic cells along the evolution of the disease [29][30] ; reports on B-CLPD cases with 2 or more distinct unrelated B-cell clones are scanty in the literature and restricted to between 1 and 3 patients at maximum. 12,15,[17][18][19]31,32 In most of these cases, biclonality was suspected based on flow cytometry immunophenotypic studies, which revealed the presence of 2 phenotypically distinct B-cell populations, 15,17 frequently displaying a different sIg light chain isotype 12,17,18,31,32 ; molecular analysis confirmed the presence of 2 unrelated malignant clones, indicating that these cases corresponded to true biclonal B-CLPD. 12,[15][16][17]31,32 Nevertheless, until now the incidence of biclonality among B-CLPD has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…12,15,[17][18][19]31,32 In most of these cases, biclonality was suspected based on flow cytometry immunophenotypic studies, which revealed the presence of 2 phenotypically distinct B-cell populations, 15,17 frequently displaying a different sIg light chain isotype 12,17,18,31,32 ; molecular analysis confirmed the presence of 2 unrelated malignant clones, indicating that these cases corresponded to true biclonal B-CLPD. 12,[15][16][17]31,32 Nevertheless, until now the incidence of biclonality among B-CLPD has not been established. The first goal of the present study was to determine this incidence; for that purpose, we have analyzed at diagnosis a large series of 477 consecutive patients suffering from leukemic B-CLPD.…”
Section: Discussionmentioning
confidence: 99%